Testing the correlation of ultrahigh energy cosmic rays with high redshift sources - Sigl, Gunter (2001)
We study the correlation between compact radio quasars or 3EG gamma-ray blazars and the arrival direction of cosmic rays above 1019 eV using an updated list of air shower detections. Our Monte Carlo simulations reveal no significant correlations above random results, and some previous positive results appear to be an effect of the small sample size. Consequently, there is no evidence for ultrahigh energy cosmic ray primaries being new particles or particles with new interactions beyond the electroweak scale, produced in high-redshift active galactic nuclei.